Nuclear Export Signal of Androgen Receptor (NES(AR)) Regulation of Androgen Receptor Level in Human Prostate Cell Lines via Ubiquitination and Proteasome-Dependent Degradation - Gong, Yanqing (Endocrine Society, 2012)
Androgen receptor (AR) plays a key role in prostate development and carcinogenesis. Increased expression and/or stability of AR is associated with sensitization of prostate cancer cells to low levels of androgens, leading to castration resistance. Hence, understanding the mechanisms regulating AR protein stability is clinically relevant and may lead to new approaches to prevent and/or treat prostate cancer. Using fluorescence microscopy, Western blot, and pulse chase assay, we showed that nuclear export signal (NES)(AR), a nuclear export signal in the ligand binding domain (LBD) of AR, can significantly enhance the degradation of fusion protein constructs in PC3 prostate cancer cells. The half-life of GFP-NES(AR) was less than 3 h, which was 10 times shorter than that of green fluorescent protein (GFP) control. Further analysis showed that NES(AR) can signal for polyubiquitination and that degradation of NES(AR)-containing fusion proteins can be blocked by proteasome inhibitor MG132. Ubiquitination of GFP-AR or GFP-LBD was suppressed in the presence of dihydrotestosterone, which is known to suppress NES(AR) while inducing nuclear localization signal 2 in AR or LBD, suggesting that the export activity of NES(AR) is required for NES(AR)-mediated polyubiquitination. Treatment with MG132 also induced aggresome formation of NES(AR)-containing fusion proteins in perinuclear regions of the transfected PC3 cells, indicating a role for NES(AR) in inducing unfolded protein responses. The above observations suggest that NES(AR) plays a key role in AR ubiquitination and proteasome-dependent degradation in prostate cancer cells.